(untitled) (Communications in Computational Physics, 2018)
The paper concerns the numerical solution for the acoustic scattering problems in a two-layer medium. The perfectly matched layer (PML) technique is adopted to truncate the unbounded physical domain into a bounded computational domain. An a posteriori error estimate based adaptive finite element method is developed to solve the scattering problem. Numerical experiments are included to demonstrate the efficiency of the proposed method.